Catalyst-free and thermal-induced S→O acetyl migration reaction to generate the polyacrylate polythiols for anticorrosion use. (10th October 2018) - Han, Jin; Chen, Cheng; Xue, Qingquan; Zheng, Yaochen; Tian, Shu; Liu, Zhixiong; Shen, Jieze; Zhong, Mingqiang
Abstract: A catalyst-free and thermal-induced S→O acetyl migration (SOAM) reaction was occasionally found and used to fabricate the polythiol corrosion inhibitor. The route to prepare the polythiols was free of catalyst and side products. Only intramolecular migration process existed, while intermolecular migration was not found. Temperature-dependent 1 H NMR experiment showed the conversion rate of the SOAM reaction was 83% at 160 °C. Further heating at higher temperature or for longer reaction time, the conversion rate did not increase. It was speculated that there was equilibrium between two reversible migrations. The prepared polythiol inhibitor contains a large amount of latent thiol groups after the SOAM reaction process. The strong CuS bonds immediately formed and made the polythiol chains firmly anchored on the copper surface when the copper metal was coated with the polythiols. Also SS bond formation reaction leads to dense crosslinking and film formation. Raman spectrum and SEM were used to characterized the protective film. A smooth and defect-free film with thickness of 1.9 μm was achieved when the copper sample was immersed in the polythiol solution for 60 min. The corrosion performance of the film is obtained by potential and impedance measurements and Tafel curves by immersing in a 3.5 wt% NaCl solution. All of the coated samples exhibited significantly lower corrosion rates than the bare copper sample, and the corrosion rate decreased as the immersion time increased. The inhibtion efficiency of the polythiol inhibitor was up to 99.3%. Neutral salt spray experiments indicated that the polythiol films provided excellent protection for over one week. The polythiols were also very stable in storage and have application in designing various polyacrylate polythiols resins. Graphical abstract: Highlights: A catalyst-free and thermal-induced S/O acetyl migration (SOAM) reaction was described. The route to prepare the polythiols was free of catalyst and side products. The polythiols were oxidized by the air to form the S-S bonds and resulted in a smooth and defect-free film. The inhibtion efficiency of the polythiol inhibitor was up to 99.3%, indicating excellent protection for copper.